2009
DOI: 10.1007/s11162-009-9140-0
|View full text |Cite
|
Sign up to set email alerts
|

Prestige Among Graduate and Professional Schools: Comparing the U.S. News’ Graduate School Reputation Ratings Between Disciplines

Abstract: Using a conceptual model, this study examines the variables associated with the U.S. News and World Report peer assessment ratings of graduate and professional schools in business, education, engineering, law, and medicine. What are the correlates of prestige among the nation's leading graduate and professional schools, and are they consistent with prior studies of prestige? Not since the studies of the 1995 National Research Council (NRC) data have scholars examined the correlates of prestige for individual g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…such studies, among others, include the ranking of (a) authors and universities publishing iB articles (Morrison and inkpen 1991;trevino et al 2010); (b) authors, institutions and discipline content of published articles in the Journal of International Business Studies (JiBs) between 1970(inkpen and Beamish 1994; (c) authors and disciplines of articles published in JIBS between 1984and 1993(chandy and Williams 1994; (d) international business schools based on the measure of faculty publication (Kumar and Kundu 2004); and (e) schools based on publication data between 1995 and 2004 for four leading international business journals (chan et al 2006). the role and importance of ranking studies is well documented in literature spanning a variety of disciplinary areas, from sociology (espeland and sauder 2007; Sauder and espeland 2009), logistics (carter et al 2009), Strategy (Baden-Fuller et al 2000), Finance (Zivney and Bertin 1992), economics (Grove and Wu 2007), Management (Devinney et al 2008;Pisani 2009;Wedlin 2007;Werner 2002), Marketing (caruana et al 2009;Linton 2004;Mitra and Golder 2008), information systems (Willcocks et al 2008), Education (Sweitzer and Volkwein 2009), Research Methods (Mills et al 2006), to International Business (Macharzina et al 2004;Macharzina et al 1993). in addition to their broad disciplinary appeal, ranking studies have consistently appeared in prestigious journals for a long period of time.…”
Section: Introductionmentioning
confidence: 99%
“…such studies, among others, include the ranking of (a) authors and universities publishing iB articles (Morrison and inkpen 1991;trevino et al 2010); (b) authors, institutions and discipline content of published articles in the Journal of International Business Studies (JiBs) between 1970(inkpen and Beamish 1994; (c) authors and disciplines of articles published in JIBS between 1984and 1993(chandy and Williams 1994; (d) international business schools based on the measure of faculty publication (Kumar and Kundu 2004); and (e) schools based on publication data between 1995 and 2004 for four leading international business journals (chan et al 2006). the role and importance of ranking studies is well documented in literature spanning a variety of disciplinary areas, from sociology (espeland and sauder 2007; Sauder and espeland 2009), logistics (carter et al 2009), Strategy (Baden-Fuller et al 2000), Finance (Zivney and Bertin 1992), economics (Grove and Wu 2007), Management (Devinney et al 2008;Pisani 2009;Wedlin 2007;Werner 2002), Marketing (caruana et al 2009;Linton 2004;Mitra and Golder 2008), information systems (Willcocks et al 2008), Education (Sweitzer and Volkwein 2009), Research Methods (Mills et al 2006), to International Business (Macharzina et al 2004;Macharzina et al 1993). in addition to their broad disciplinary appeal, ranking studies have consistently appeared in prestigious journals for a long period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, different studies also showed the chance that the reputation of a parent school is often caused, in part, by the professional schools (business, law, and medical) that they have (Devinney, Dowling, Perm-Ajchariyawong, & Dowling, 2006). Sweitzer and Volkwein (2009) have argued that, at the undergraduate and graduate levels, size and admissions statistics (selectivity) are the main drivers of institutional reputation.…”
Section: Business Schools and Reputationmentioning
confidence: 99%
“…However, at the business school level size, student quality, and rankings have become the main keys behind institutional reputation (Rindova et al, 2005;Safon, 2007Safon, , 2009Sweitzer & Volkwein, 2009). Rindova et al (2005) put forth a model for organizational reputation that they applied to business schools in the United States.…”
Section: Business Schools and Reputationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, they seemed to confirm that reputational surveys, such as the one generated by USNWR, are highly variable because of the vague manner in which standards of quality are measured and the erratic methodologies used. [2][3][4] Discouraged, I considered other options (albeit, facetiously): bribe my colleagues (unethical); curry favor with every other college of pharmacy administrator I meet (difficult to do and inconsistent with my brusque personality); or populate every college administrative structure with our alumni (impossible in such a short time frame).…”
mentioning
confidence: 99%